Basic Mechanical Engineering, 1/e. - Kumar, Pravin (2013)
Basic Mechanical Engineering covers a wide range of topics and engineering concepts that are required to be learnt as in any undergraduate engineering course. Divided into three parts this book lays emphasis on explaining the logic and physics of critical problems to develop analytical skills in students.
11.2.9 Centroid of Semicircular-Section of a Disc.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books